2021
DOI: 10.1001/jama.2021.20178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mediterranean Diet or Mindfulness-Based Stress Reduction on Prevention of Small-for-Gestational Age Birth Weights in Newborns Born to At-Risk Pregnant Individuals

Abstract: IMPORTANCE Being born small for gestational age (SGA) is a leading cause of perinatal morbidity and mortality with no effective prevention or therapy. Maternal suboptimal nutrition and high stress levels have been associated with poor fetal growth and adverse pregnancy outcomes. OBJECTIVE To investigate whether structured interventions based on a Mediterranean diet or mindfulness-based stress reduction (stress reduction) in high-risk pregnancies can reduce the percentage of newborns who were born SGA and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 40 publications
1
85
0
Order By: Relevance
“…There are still very few studies correlating MD in pregnancy and the development of malformations in the unborn fetus, as few are the evidence correlating maternal MD adherence to fetal growth restriction, risk of SGA newborn and preterm delivery. [ 17 ]. Currently, there is only one randomized controlled study that implemented an early nutritional intervention with MD supplementation with extra virgin olive oil and pistachios, resulting in a significant reduction in preterm birth rate [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are still very few studies correlating MD in pregnancy and the development of malformations in the unborn fetus, as few are the evidence correlating maternal MD adherence to fetal growth restriction, risk of SGA newborn and preterm delivery. [ 17 ]. Currently, there is only one randomized controlled study that implemented an early nutritional intervention with MD supplementation with extra virgin olive oil and pistachios, resulting in a significant reduction in preterm birth rate [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research gap was partially filled by a Spanish randomized control trial conducted on three groups of women with high-risk pregnancies who underwent either MD or mindfulness-based stress reduction interventions versus usual care. The study showed that the percentage of newborns with birth weight below the 10th percentile dropped significantly in the groups that received either one or the other intervention [ 17 ].…”
Section: MD and Pregnancymentioning
confidence: 99%
“…The main results of this trial have been previously described [ 26 ] and the study protocol has been described elsewhere [ 27 ]. For the present analysis, from the total sample of 1221 randomized participants, 215 participants were excluded because of missing data on dietary information, and 36 participants showed extreme energy intake outside predefined limits [ 28 ], including 970 participants at high risk of developing SGA during pregnancy in the final dataset ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Newborns’ birthweight: Birthweight percentile was calculated with birthweight adjusted by gestational age at delivery and gender, according to standards for the Spanish population [ 26 ]. SGA was defined as birthweight below the 10th percentile, severe SGA as birthweight below the 3rd percentile [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation